Over‐expression of human cytomegalovirus miR‐US25‐2‐3p downregulates eIF4A1 and inhibits HCMV replication. Issue 14 (6th June 2013) - Qi, Manlong; Qi, Ying; Ma, Yanping; He, Rong; Ji, Yaohua; Sun, Zhengrong; Ruan, Qiang
Abstract : It has been reported that human cytomegalovirus (HCMV) miR‐US25‐2 reduces DNA viral replication including HCMV. However, the mechanism remains unknown. In our study, eukaryotic translation initiation factor 4A1 ( eIF4A1 ) was identified to be a direct target of miR‐US25‐2‐3p. Small interfering RNA (siRNA) and miR‐US25‐2‐3p mediated eIF4A1 knockdown experiments revealed that high level of miR‐US25‐2‐3p in MRC‐5 cells decreased HCMV and host genomic DNA synthesis, and inhibited cap‐dependent translation and host cell proliferation. However, eIF4A1 up‐regulation induced by miR‐US25‐2‐3p inhibitor increased HCMV copy number. Therefore, the over‐expression of miR‐US25‐2‐3p and consequent lower expression of eIF4A1 may contribute to the inhibition of HCMV replication. Abstract : eIF4A1 is the direct target gene of miR‐US25‐2‐3p. Over‐expression of miR‐US25‐2‐3p inhibits HCMV replication by targeting eIF4A1 . Over‐expression of miR‐US25‐2‐3p decreases eIF4A1 ‐mediated translation. miR‐US25‐2‐3p significantly inhibits host cell proliferation and genomic DNA synthesis.